Testicular Tumor in Children: A Rare Case Report - Severino Rey Nodar; Sirced Salazar; Carlos Cárdenas; Verónica García Yllán (Current Practice in Medical Science Vol. 9, 2022)
Male genital tract mesenchymal neoplasms are uncommon, with the majority occurring in the paratesticular and testicular adnexa. The most common sarcomas in children with this location are paratesticular embryonal rhabdomyosarcoma (RMS). Without any personal pathological history, a 4-year-old boy reported pain and a 2 month-old rise in the size of his left testicle. Physical examination revealed that the left scrotal sac was swollen, uncolored, indurated, and not particularly uncomfortable. No changes were visible in the right testicle. The RMS is the second most common soft tissue tumour in children, after the head and neck region, and it most frequently develops in the genitourinary system. It is rare to develop primary intratesticular rhabdomyosarcoma.